Light and electron microscopic observations on effects of tribendimidin on cuticle of Necator americanus and small intestinal mucosa of infected golden hamsters - Xiao Shu-hua; Ren Hai-nan; Dai Zhi-qiang; Yang Yuan-qing; Zhang Chao-wei (Acta Pharmacologica Sinica, 2016)
Golden hamsters infected with Necator americanus were treated orally with a new anthilmintic tribendimidin (N, N'-[bis-4'-(1-dimethyl amino ethylidene amino)phenyl] 1,4-phenyene dimethylidyne amine) at a single dose of 150 mg/kg. One h after medication, some worms showed cuticular swelling, fusion of transverse striations and attachment of host leucocytes onto the worm's damaged cuticular surface. Four h post treatment, the cuticle revealed a moderate swelling or even erosion. Meanwhile, the ventral cutting plates appeared to be swollen. After 8-24 h, severe cuticular swelling, erosion and peeling in female worm tails and male copulatory bursa were seen. No increases in lesions in the small intestinal mucosa of infected golden hamsters were observed 4-8 h after medication.